Association of rheumatoid arthritis with bronchial asthma and asthma-related comorbidities: A population-based national surveillance study - Kim, Jung Gon; Kang, Jiyeon; Lee, Joo-Hyun; Koo, Hyeon-Kyoung (Frontiers in Medicine, 2023)
Background: The aim of this study was to investigate the impact of rheumatoid arthritis (RA) on the prevalence of bronchial asthma and asthma-related comorbidities. We also aimed to identify the influence of RA on interrelationship between asthma and asthma-related comorbidities. Methods: From the Korean National Health and Nutrition Examination Survey, participants >40 years of age who completed questionnaires and spirometry tests were enrolled. Patient data on RA, asthma, allergic rhinitis, atopic dermatitis, chronic obstructive pulmonary disease (COPD), sinusitis, otitis media, and body mass index (BMI) were collected. Logistic regression and network analyses were performed. Results: A total of 14,272 subjects were enrolled, among which, 334 (2.4%) had RA. RA was significantly associated with asthma (OR 2.32; 95% CI 1.51–3.57), allergic rhinitis (OR 1.51; 95% CI 1.08–2.10), and sinusitis (OR 1.64; 95% CI 1.08–2.50). The network analysis revealed an interrelationship between asthma and allergic rhinitis, sinusitis, otitis media, atopic dermatitis, RA, and BMI. The interrelationship between asthma and sinusitis was stronger in the RA group. Of note, the relationship between asthma and BMI was distinctively found only in the RA group (r = 0.214, P <0.05). In patients with asthma, the prevalence of obesity was 64% in the presence of RA, and 34% in the absence of RA (P = 0.034). Conclusions: This study supports the positive association of RA with asthma, allergic rhinitis, and sinusitis. Our analysis suggests a notable interrelationship between the presence of asthma and higher BMI values in patients with RA, indicating that asthma is more obesity-related in patients with RA.